2014
DOI: 10.18869/acadpub.jnms.1.2.14
|View full text |Cite
|
Sign up to set email alerts
|

Family-oriented empowerment model influencing quality of life CABG patients

Abstract: Background and Purpose: Heart disease death rates have increased worldwide.Family-oriented empowerment model

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The literature review on empowerment of patients with CAD showed that a higher level of patient empowerment during the treatment process resulted in improved self-care 9,20,29,36. This ultimately led to increased patient satisfaction,29,34,37 a positive health status,24,28 improved sense of coherence,29,37 improved self-efficacy,24,28 and a better quality of life 9,38…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The literature review on empowerment of patients with CAD showed that a higher level of patient empowerment during the treatment process resulted in improved self-care 9,20,29,36. This ultimately led to increased patient satisfaction,29,34,37 a positive health status,24,28 improved sense of coherence,29,37 improved self-efficacy,24,28 and a better quality of life 9,38…”
Section: Resultsmentioning
confidence: 99%
“…Small et al44 reported that patients (mostly cardiovascular, articular, or diabetic patients) with long-term conditions need to develop a personal strategy to control and manage their disease accordingly. Patients have been assumed to experience the illness continuously, and this assumption affects the patient, their family, as well as the community 38. Therefore, health care professionals should encourage patients to manage and gain greater control of their disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations